Comparison of three different diffractıve multifocal intraocular lenses with a +2.5, +3.0, and +3.75 diopter additıon power - Altinkurt, Emre (Saudi J Ophthalmol, 2019)
PURPOSE: To compare the functional outcomes and astigmatic tolerability after implantation of multifocal intraocular lenses (IOLs) with a +2.5, +3.0, and +3.75 diopter (D) addition power. METHODS: This study included 122 eyes of 61 patients who had bilateral cataract extraction and implantation of diffractive aspheric multifocal acrylic IOLs with +2.5 D (+2.5 group), +3.0 D (+3.0 group), and +3.75 D (+3.75 group) addition powers. 1-year after surgery, distance corrected near (DNVA) and intermediate (DIVA) visual acuities at 32, 40, 45, 50, 55, and 60 cm; and contrast sensitivity measurements under photopic, mesopic and mesopic with glare conditions; spherical and astigmatic defocus testing; distance-intermediate-near vision patient satisfaction levels; spectacle dependance; patient-reported outcomes were assessed binocularly. RESULTS: The +2.50 D group had better DIVA than both +3.0 group and +3.75 groups at 45 cm, 50 cm, 55 cm, and 60 cm (p < 0.05). The +3.75 group had better DNVA than both +2.5 and +3.0 IOL groups at 32 cm (p < 0.05). There was no significant difference in mean contrast values at all frequencies between three IOL groups (p > 0.05). The +2.50 D group showed better astigmatic tolerability than +3.00 group (at 2.00 D) and +3.75 group (at 1.50 D, and at 2.00 D) (p < 0.05). CONCLUSION: Multifocal IOLs with +2.5 add power have better intermediate vision, but worse near vision compared to multifocal IOLs with +3.00 D and +3.75 D add power. Multifocal IOLs with +2.50 D add power tend to have better astigmatic defocus tolerability than multifocal IOLs with +3.00 D and +3.75 D add powers.